Method for preparing calcium sulfate from biogas slurry wastewater
By using the method of preparing calcium sulfate with sterilized wastewater, the problems of high cost of calcium sulfate preparation, environmental pollution and low purity in the prior art are solved, and high-efficiency, low-cost and environmentally friendly preparation of high-purity calcium sulfate is achieved.
Patent Information
- Application Number
- CN202411953401.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-12-26
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-08
AI Technical Summary
The existing calcium sulfate preparation methods have problems such as high cost, environmental pollution and low product purity, especially in natural gypsum mining and chemical synthesis methods.
The method of preparing calcium sulfate using the wastewater of sterilization was adopted, and the white calcium sludge was fully reacted with dilute sulfuric acid and calcined to obtain high-purity calcium sulfate.
It has achieved efficient, low-cost and environmentally friendly preparation of high-purity calcium sulfate, solving the problems of resource consumption and environmental pollution in traditional methods.
Smart Images

Figure CN119774651A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of inorganic material preparation, and in particular to a method for preparing calcium sulfate by utilizing biogas slurry wastewater. Background Art
[0002] Humans have been using calcium sulfate for thousands of years. In biomedicine, calcium sulfate has the effects of clearing away heat and detoxifying, and promoting sleep and calming the mind. Ancient Chinese medicine used it to treat fever, hot cough, and relieve symptoms of thirst and constipation. Modern medicine has found that it has good biocompatibility, no foreign body stimulation to surrounding tissues, can self-solidify in situ, has good hemostatic effect, guides tissue regeneration, induces bone formation, is non-toxic and can be completely degraded, and is widely recognized as a promising bone transplant substitute. In addition, calcium sulfate has good gelling properties, can be soundproof and heat-insulating, and has certain flame retardancy. In food production, it can be used as a food coagulant; in agriculture and forestry, it can be used to produce ammonium sulfate fertilizers, or as a soil conditioner to improve the pH of the soil; in the chemical industry, calcium sulfate can be used to produce sulfate products; in the building materials industry, it can be used as a retarder to produce cement, and can also be directly used to produce wall materials or other building materials; in ceramic manufacturing and machinery industries, it is used to make molds, crafts and sculptures. According to different application fields, calcium sulfate can be divided into the following four categories: industrial grade, food grade, medical grade and surgical implant grade. At present, the first two types of calcium sulfate have been industrialized in China, and there are reports of domestic production of medical grade calcium sulfate, while surgical implant grade calcium sulfate is still in the laboratory research stage and the product is completely dependent on imports.
[0003] For a long time, calcium sulfate has been mainly derived from the mining and processing of natural gypsum. Natural gypsum resources are relatively concentrated, and the mining process requires a lot of manpower, material and financial resources for mining, ore transportation and preliminary processing. In addition, the quality of natural gypsum is greatly affected by geological conditions, and there are large differences in its purity, crystal form and impurity content, which leads to more complex purification and processing technology in subsequent applications, increasing production costs. At the same time, excessive exploitation of natural gypsum resources will cause damage to the ecological environment, such as causing surface collapse, destroying vegetation and other problems, which is not conducive to sustainable development.
[0004] Chemical synthesis is also a common way to prepare calcium sulfate, for example, sulfuric acid is reacted with calcium salts (such as calcium chloride, calcium carbonate, etc.) to generate calcium sulfate. However, this method has high raw material cost, a large amount of by-products (such as hydrogen chloride gas, etc.) are easily produced during the reaction, and subsequent treatment is required, and the reaction conditions (such as temperature, concentration, pH value, etc.) are strictly controlled, and the purity and crystal quality of the calcium sulfate product will be affected if not carefully. Moreover, chemical synthesis usually requires the use of a large amount of chemical reagents, which not only increases production costs, but also may pollute the environment.
[0005] In the traditional production of calcium sulfate, the raw materials used to produce calcium sulfate may contain a variety of impurities. For example, natural gypsum ore contains clay, organic matter, carbonate and other impurities in addition to calcium sulfate. During the production process, these impurities are difficult to completely remove, resulting in a decrease in the purity of the calcium sulfate product. At the same time, clay impurities will make the color of the calcium sulfate product gray, affecting its appearance and quality. The shortcomings of the traditional calcium sulfate production process result in low whiteness and purity of the produced calcium sulfate. The purity of ordinary industrial-grade calcium sulfate is generally around 70%-90%, and the whiteness is generally around 70%-85%. The Chinese invention patent with announcement number CN114197028B provides a continuous preparation method for calcium sulfate whiskers, which uses gypsum as a raw material to prepare calcium sulfate with a whiteness greater than 80.
[0006] In summary, the existing calcium sulfate preparation methods all have limitations to varying degrees. Therefore, developing a new preparation process that is efficient, low-cost, environmentally friendly and can stably prepare high-quality calcium sulfate products has important practical significance and broad application prospects. Summary of the invention
[0007] In view of this, the object of the present invention is to provide a method for preparing calcium sulfate using biogas wastewater.
[0008] The objective of the present invention is achieved through the following technical solutions:
[0009] <First aspect>
[0010] The present invention provides a method for preparing calcium sulfate by utilizing biogas slurry wastewater, comprising the following steps:
[0011] The dried white lime mud powder and deionized water are prepared into a suspension having a solid content of 15-25%;
[0012] Adding dilute sulfuric acid to the suspension at 60-100° C. to fully react, and filtering, washing, and drying the reaction product to obtain an intermediate sample;
[0013] The intermediate sample is calcined at 300-400° C. for 1.5-2.5 hours and then cooled to obtain the calcium sulfate.
[0014] As an implementation scheme, the white lime mud is obtained by using biogas slurry wastewater. After the biogas slurry wastewater is flocculated and precipitated, an alkaline substance is used for pH adjustment treatment, and then solid-liquid separation is performed. The obtained precipitate is the white lime mud, and the alkaline substance is calcium oxide.
[0015] As an implementation scheme, the flocculation and precipitation of the biogas slurry wastewater is as follows: a coagulant, calcium oxide and a flocculant are sequentially added to the biogas slurry wastewater, flocculation and precipitation treatment is performed, and then solid-liquid separation is performed to obtain a first section of wastewater, wherein the coagulant includes polyferric sulfate and the flocculant is PAM, and an alkaline substance is added to the first section of wastewater for pH adjustment.
[0016] As an embodiment, the white lime mud contains, by mass, 52 to 64 parts of calcium sulfate, 12 to 16 parts of calcium carbonate, and 23 to 33 parts of impurities, wherein the impurities include iron hydroxide, silicon oxide, magnesium carbonate, and organic matter.
[0017] As an embodiment, the impurities include 3 to 5 parts of iron hydroxide, 0.3 to 0.5 parts of silicon oxide, 2.3 to 3 parts of magnesium carbonate and 18 to 24 parts of organic matter.
[0018] As an implementation scheme, the dried lime mud is ground and pulverized to obtain lime mud powder with a size of less than 200 meshes, and then the suspension is prepared.
[0019] In some embodiments, the solid content of the suspension is 20%.
[0020] In some embodiments, the reaction temperature of adding dilute sulfuric acid to the suspension is 80°C.
[0021] As an embodiment, the concentration of the dilute sulfuric acid is 4 to 6 mol / L.
[0022] In some embodiments, the concentration of dilute sulfuric acid is 5 mol / L.
[0023] As an embodiment, the dilute sulfuric acid is added in a stepwise manner, with 1 to 2 mL added each time, and the pH value is tested after sufficient stirring.
[0024] In some embodiments, the amount of the dilute sulfuric acid added each time is 1 mL.
[0025] As an implementation scheme, the pH value is used to judge whether the reaction is complete. When the pH value of the reaction system is close to 7, the pH value suddenly changes after adding dilute sulfuric acid again, indicating that the reaction is complete.
[0026] In some embodiments, the calcination temperature is 350° C. and the calcination time is 2 h.
[0027] As an embodiment, the biogas wastewater also includes alkalinity (mainly including CO3 2- 、HCO3 - ).
[0028] As an embodiment, the amount of polyferric sulfate added is 25 to 40 L per cubic meter of wastewater.
[0029] In some embodiments, the amount of polyferric sulfate added is 33 L per cubic meter of wastewater.
[0030] As an embodiment, the amount of calcium oxide added is 5-10 kg per cubic meter of wastewater.
[0031] In some embodiments, the amount of calcium oxide added is 6 kg per cubic meter of wastewater.
[0032] As an embodiment, the amount of PAM added is 10 to 15 L of PAM aqueous solution per cubic meter of wastewater, and the concentration of the PAM aqueous solution is 2 to 3 wt.‰.
[0033] In some embodiments, the amount of PAM added is 13 L of PAM aqueous solution per cubic meter of wastewater, and the concentration of the PAM aqueous solution is 2.5 wt.‰.
[0034] As an embodiment, the precipitated sludge after solid-liquid separation after the flocculation sedimentation treatment is ferrocalcium sludge.
[0035] As an embodiment, the method of obtaining calcium-iron mud by solid-liquid separation includes plate and frame pressing.
[0036] In some embodiments, the plate and frame pressing time is 3 to 4 hours.
[0037] As an embodiment, the liquid obtained by solid-liquid separation after the pH adjustment treatment is the second-stage wastewater.
[0038] As an implementation plan, the second stage wastewater is subjected to ammonia nitrogen removal treatment to obtain the third stage wastewater, and the ammonia-containing waste gas generated during the treatment process is absorbed by dilute sulfuric acid to obtain an ammonium sulfate solution; the pH value of the third stage wastewater is adjusted, and then biochemical treatment is carried out or the biochemical treatment process is connected with a membrane treatment process such as NF nanofiltration to make the wastewater meet the discharge standard requirements.
[0039] As an embodiment, the alkaline substance is calcium oxide.
[0040] As an embodiment, the amount of the alkaline substance added is 5-10 kg per cubic meter of wastewater.
[0041] In some embodiments, the amount of alkaline substance added is 6 kg per cubic meter of wastewater.
[0042] As an embodiment, the pH of the second stage wastewater is 11-12.
[0043] As an embodiment, carbon dioxide is introduced into the third stage wastewater to adjust the pH to 8-9.
[0044] The biochemical treatment process is a multi-stage AO+MBR membrane treatment process, or a multi-stage AO+MBR membrane treatment process connected with a NF nanofiltration treatment process. In the biochemical treatment process, according to the requirements of the biogas slurry treatment standard, the NF nanofiltration treatment process can be connected to meet the requirements of the biogas slurry discharge standard.
[0045] As an implementation scheme, the biogas slurry wastewater includes COD, SS (suspended solids), TP (total phosphorus), and ammonia nitrogen. The content of each component is: COD 8000-20000 mg / L, ammonia nitrogen 1500-4000 mg / L (total nitrogen ~ 5000 mg / L), TP (total phosphorus) ~ 150 mg / L.
[0046] As an implementation plan, in the first section of wastewater, the treatment efficiency of COD is 70-90%, the treatment efficiency of SS is 90-96%, the treatment efficiency of TP is 85-95%, the treatment efficiency of ammonia nitrogen is 15%-25%, and the treatment efficiency of total nitrogen is 15%-25%.
[0047] As an implementation plan, in the second section of wastewater, the treatment efficiency of COD is 5-15%, the treatment efficiency of SS is 80%-90%, the treatment efficiency of TP is 40-60%, the treatment efficiency of ammonia nitrogen is 2-6%, and the treatment efficiency of total nitrogen is 2-5%.
[0048] As an embodiment, in the third stage wastewater, the treatment efficiency of ammonia nitrogen is 85-95%, and the treatment efficiency of total nitrogen is 80-95%.
[0049] As an embodiment, the iron-calcium mud is used to prepare a carbon / gamma iron oxide chimera desulfurizer.
[0050] As an embodiment, the white lime mud is used to prepare a hydroxy-containing iron oxide desulfurizer.
[0051] As an embodiment, the ammonium sulfate solution is used to extract ammonium sulfate.
[0052] <Second Aspect>
[0053] The invention provides calcium sulfate, which is prepared by the method for preparing calcium sulfate by utilizing biogas slurry wastewater. The purity of the calcium sulfate reaches 99.1wt.% and the whiteness exceeds 95%.
[0054] <Third Aspect>
[0055] The present invention also provides a method for preparing a desulfurizing agent containing iron oxide containing hydroxyl, which is a method for preparing the desulfurizing agent using the iron calcium mud obtained in the method for preparing calcium sulfate from the above-mentioned biogas slurry wastewater, that is, a method for preparing calcium sulfate from biogas slurry wastewater and co-producing a desulfurizing agent containing iron oxide containing hydroxyl. The method comprises the following steps:
[0056] The dried calcium iron mud powder is aerobically calcined at 150-200° C. for 2-3 hours, and then cooled to room temperature to obtain calcium iron mud aerobically calcined;
[0057] The aerobic calcined calcium iron mud is placed in a strong alkali aqueous solution for washing, then rinsed with deionized water until neutral, and dried to obtain the calcium iron mud after alkali washing, which is the hydroxyl-containing iron oxide desulfurizer;
[0058] As an embodiment, the iron-calcium mud contains, by mass, 14 to 24 parts of calcium sulfate, 4 to 7 parts of calcium carbonate, 26 to 43 parts of iron oxyhydroxide, 1.1 to 1.9 parts of silicon oxide, 0.5 to 0.9 parts of magnesium carbonate and 27 to 53 parts of organic matter.
[0059] As an embodiment, the dried calcium iron mud is first ground to obtain dry calcium iron mud with a mesh size below 200, and then subjected to the aerobic calcination.
[0060] As an embodiment, the ferric calcium mud after alkali washing is ground to obtain a hydroxyl-containing iron oxide desulfurizer with a mesh size of less than 200.
[0061] As an embodiment, the mass ratio of the aerobic calcined calcium iron mud and the aqueous solution of the strong alkali is 3:(6-8), and the concentration of the aqueous solution of the strong alkali is 8 mol / L to saturation.
[0062] In some embodiments, the mass ratio of the aerobic calcined calcium iron mud to the aqueous solution of strong alkali is 3:7, and the concentration of the aqueous solution of strong alkali is 10 mol / L to 15 mol / L.
[0063] As an embodiment, the strong base is NaOH or KOH.
[0064] In some embodiments, the strong base is NaOH.
[0065] In some embodiments, the temperature of the aerobic calcination is 200° C., and the calcination time is 2 hours.
[0066] <Fourth Aspect>
[0067] The present invention provides a hydroxyl-containing iron oxide desulfurizer, which is prepared by the preparation method of the hydroxyl-containing iron oxide desulfurizer, and the components are as follows by weight:
[0068] Calcium sulfate: 28-35 parts;
[0069] Iron oxyhydroxide: 50-62 parts;
[0070] Impurities: 11 to 14 parts.
[0071] As an embodiment, the impurities include SiO2, CaCO3, and MgCO3.
[0072] As an embodiment, the components of the oxyhydroxide-containing iron desulfurizer are: calcium sulfate: 31.35 parts; oxyhydroxide iron: 56.08 parts; impurities: 12.57 parts.
[0073] <Fifth Aspect>
[0074] The present invention also provides a method for preparing a carbon / γ-iron oxide chimera desulfurizer, which is a method for using the iron-calcium mud produced in the above-mentioned method for preparing calcium sulfate from biogas slurry wastewater to prepare a carbon / γ-iron oxide chimera desulfurizer, that is, a method for preparing calcium sulfate from biogas slurry wastewater and co-producing a carbon / γ-iron oxide chimera desulfurizer.
[0075] A method for preparing a carbon / gamma iron oxide chimera desulfurizer comprises the following steps:
[0076] The dried calcium iron mud is subjected to oxygen-free calcination at 550-650° C. for 2.5-3.5 hours, and then subjected to aerobic calcination at 200-500° C. for 1.5-2.5 hours. After cooling to room temperature, the carbon / γ-iron oxide chimera desulfurizer is obtained.
[0077] As an embodiment, the carbon / γ iron oxide chimera desulfurization agent is ground and pulverized to obtain a carbon / γ iron oxide chimera desulfurization agent with a size not exceeding 200 meshes.
[0078] As an embodiment, during the oxygen-isolated calcination treatment, the dried calcium iron mud is pressed to a density of 3.0 to 3.5 g / cm3, and the crucible cover is bonded to the crucible and to the powder in the crucible.
[0079] In some embodiments, the temperature of the oxygen-isolated calcination is 600° C., and the calcination time is 3 hours.
[0080] In some embodiments, the temperature of the aerobic calcination is 400° C., and the calcination time is 2 hours.
[0081] <Sixth Aspect>
[0082] The present invention also provides a method for preparing a carbon / γ-iron oxide chimera desulfurizer using biogas slurry wastewater, which is a method for preparing a carbon / γ-iron oxide chimera desulfurizer using the iron calcium mud produced in the preparation of a hydroxyl-containing iron oxide desulfurizer using biogas slurry wastewater, that is, a method for preparing calcium sulfate using biogas slurry wastewater and co-producing a carbon / γ-iron oxide chimera desulfurizer. The steps are as follows:
[0083] The dried calcium iron mud is subjected to a hydrothermal reaction at 180-220° C. for 2.5-3.5 hours, and then subjected to an aerobic calcination treatment at 200-500° C. for 1.5-2.5 hours. After cooling to room temperature, the carbon / γ-iron oxide chimera desulfurizer is obtained.
[0084] As an embodiment, the solid-liquid mass ratio during the hydrothermal reaction is 1:3-5.
[0085] In some embodiments, the solid-liquid mass ratio of the hydrothermal reaction is 1:5.
[0086] As an embodiment, during the hydrothermal reaction and the aerobic calcination, the heating rate is 5 to 10°C / min.
[0087] In some embodiments, the heating rate is 10° C. / min.
[0088] In some embodiments, the temperature of the hydrothermal reaction is 200° C. and the reaction time is 3 h.
[0089] In some embodiments, the temperature of the aerobic calcination is 280° C. and the reaction time is 2 h.
[0090] As an embodiment, the product after oxygen calcination and cooling is ground to obtain the carbon / γ-iron oxide chimera with a size of less than 200 meshes.
[0091] <Seventh Aspect>
[0092] The present invention provides a carbon / γ-iron oxide chimera desulfurizer, which is prepared by the preparation method of the carbon / γ-iron oxide chimera desulfurizer, and the components are as follows by weight:
[0093] Carbon: 13-17 parts;
[0094] Gamma iron oxide: 40-50 parts;
[0095] Calcium sulfate: 25-32 parts;
[0096] Calcium carbonate: 7-9 parts;
[0097] Impurities: 2.5 to 3.5 parts.
[0098] As an embodiment, the impurities include SiO2 and MgCO3.
[0099] As an embodiment, the carbon / γ iron oxide chimera desulfurizer comprises the following components by mass: carbon: 15-16.5 parts; γ iron oxide: 45-46 parts; calcium sulfate: 27-28.5 parts; calcium carbonate: 8-9 parts; and impurities: 3-3.2 parts.
[0100] In some embodiments, a carbon / γ iron oxide chimera desulfurizer comprises the following components by mass: carbon: 15.18 parts; γ iron oxide: 45.33 parts; calcium sulfate: 28.19 parts; calcium carbonate: 8.16 parts; and impurities: 3.14 parts.
[0101] In some embodiments, a carbon / γ iron oxide chimera desulfurizer comprises the following components by mass: carbon: 16.28 parts; γ iron oxide: 45.33 parts; calcium sulfate: 27.19 parts; calcium carbonate: 8.11 parts; impurities: 3.09 parts, including SiO2 and MgCO3.
[0102] <Eighth Aspect>
[0103] The present invention provides a method for preparing ammonium sulfate, which is a method for preparing ammonium sulfate by using the ammonium sulfate solution produced in the method for preparing calcium sulfate by using biogas slurry wastewater, that is, a method for preparing calcium sulfate by using biogas slurry wastewater and co-producing ammonium sulfate.
[0104] The components of the ammonium sulfate solution are as follows, by mass: 40 to 50 parts of ammonium sulfate and 50 to 60 parts of water.
[0105] A method for preparing ammonium sulfate comprises the following steps:
[0106] An ethanol solution is added to the ammonium sulfate solution at a rate of 5 to 20 mL / min, and the mixture is continuously stirred until crystals are completely precipitated. Then, solid-liquid separation is performed, and the obtained solid matter is washed and dried with the ethanol solution to obtain the ammonium sulfate with a purity exceeding 99%.
[0107] As an embodiment, the concentration of the ethanol solution is not less than 75 vol.%.
[0108] As an embodiment, the ethanol-water solution after the solid-liquid separation is separated by a pervaporation membrane to obtain ethanol solution and water that can be recycled.
[0109] In some embodiments, the ethanol solution is added at a rate of 5 mL / min.
[0110] In some embodiments, the mass ratio of the added ethanol solution to the ammonium sulfate solution is 1.5:1.
[0111] Compared with the prior art, the present invention has the following beneficial effects:
[0112] The present invention discloses a method for preparing calcium sulfate by purifying white lime mud. Organic matter attached to the white lime mud is removed by pickling and calcining. The purity of the prepared calcium sulfate reaches 99.1wt.%, and the whiteness exceeds 95%. The calcium sulfate can be used as an additive for biogas residue fertilizer, and can also be processed into building materials and the like. BRIEF DESCRIPTION OF THE DRAWINGS
[0113] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0114] Figure 1 This is a picture of the pickling and drying process in Example 1 of the present invention, wherein a picture of a state after adding dilute sulfuric acid in step S13 ( Figure 1 (a)) and photos after water bath heating ( Figure 1 (b)) and the sample after drying in step S34 ( Figure 1 (c));
[0115] Figure 2 is the amount before calcination in step S15 in Example 1 of the present invention ( Figure 2 (a)) and after calcination ( Figure 2 (b)) Sample photos;
[0116] Figure 3 A schematic diagram of a processing system used in step S11 in Example 1 of the present invention;
[0117] Figure 4 This is a flow chart of the method for treating biogas slurry wastewater in Example 1 of the present invention;
[0118] Figure 5 This is the XRD test diagram of the calcium sulfate sample prepared in Example 1 of the present invention;
[0119] Figure 6 This is a SEM test image of the calcium sulfate sample prepared in Example 1 of the present invention.
[0120] Figure 7 The calcium iron mud before aerobic calcination in step S22 of Example 2 of the present invention ( Figure 7 (a)) and after aerobic calcination ( Figure 7 (b)) Sample photos;
[0121] Figure 8 This is a SEM image of the iron oxide desulfurizer containing hydroxyl prepared in Example 2 of the present invention, wherein Figure 8 (a) scale bar: 100 nm, Figure 8 (b) scale bar 500nm, Figure 8 (c) Scale bar: 1 μm, Figure 8 Scale bar in (d) 5 μm;
[0122] Fig. 9 This is a SEM image of the iron oxide desulfurizer containing hydroxyl prepared in Example 2 of the present invention, wherein Fig. 9 (a) scale bar: 100 nm, Fig. 9 (b) scale bar 500nm, Fig. 9 (c) Scale bar: 1 μm, Fig. 9 Scale bar in (d) 2 μm;
[0123] Fig.10 The calcined calcium iron mud in step S22 of Example 2 of the present invention ( Fig.10 (a)) and the iron oxyhydroxide desulfurizing agent ( Fig.10 (b)) spectrum;
[0124] Fig.11 is the amount before calcination in step S32 in Example 3 of the present invention ( Fig.11 (a)) and after calcination ( Fig.11 (b)) Sample photos;
[0125] Fig.12 This is a photo of the calcined product in step S33 in Example 3 of the present invention;
[0126] Fig.13 This is a SEM image of the carbon / γFe2O3 chimera desulfurizer prepared in Example 3 of the present invention, wherein Fig.13 The scale bar in (a) is 100 nm. Fig.13 The scale bar in (b) is 100 nm. Fig.13 The scale bar in (c) is 200 nm. Fig.13 The scale bar in (d) is 300 nm; DETAILED DESCRIPTION
[0127] The present invention is described in detail below in conjunction with embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, some adjustments and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0128] Example 1
[0129] The present embodiment provides a method for preparing calcium sulfate using biogas wastewater. The wastewater comes from a biogas station in Funan County, Fuyang City, Anhui Province. The wastewater is first pretreated, including intercepting large solid impurities with a grid and removing larger particles in the wastewater by gravity sedimentation. This is a routine operation in wastewater treatment and will not be described in detail here. In the present embodiment, the wastewater with obvious particles removed is used as the source wastewater.
[0130] A method for preparing calcium sulfate using biogas wastewater comprises the following steps:
[0131] S11, coagulating, flocculating and precipitating the source wastewater, performing a first solid-liquid separation, and obtaining a first section of wastewater; performing a pH adjustment treatment on the first section of wastewater, performing a second solid-liquid separation, and obtaining a precipitated mud (also called white lime mud); drying the white lime mud in an oven at 100° C. to a constant weight, grinding and passing through a 200-mesh sieve, retaining the sieved material, and the whiteness of the sieved material is 81.30;
[0132] S12, adding deionized water to the white lime mud after step S11 to prepare a suspension with a solid content of 20%, and testing the pH value of the suspension to find that it is 11.92;
[0133] S13, heat the suspension in a water bath at 80°C for 3h. During the water bath, stir the suspension continuously at 300r / min using a stirrer, and slowly add 5mol / L dilute sulfuric acid until the pH value drops below 7, then stop adding dilute sulfuric acid. Figure 1 (a) shows a state photo after adding dilute sulfuric acid. Figure 1 (b) shows the photograph after heating in a water bath for 3 h;
[0134] S14, the pH-adjusted suspension was filtered using a vacuum filtration device to obtain a solid substance, which was then washed with deionized water for multiple times until the supernatant was clear to obtain a washed solid, which was then dried in an oven at 105° C. to a constant weight to obtain a calcium sulfate intermediate sample such as Figure 1 As shown in (c), the whiteness is 91.11;
[0135] S15. Grind the intermediate sample into powder, place it in a box-type electric furnace, calcine it at 350°C for 2 hours, and then cool it to room temperature to obtain a calcium sulfate sample with a whiteness of 96.00. The photos of the samples before and after calcination are as follows: Figure 2 shown.
[0136] Compared with the sample in step S11, the whiteness of the intermediate sample after acid washing in step S14 increased by about 12%, indicating that impurities were reduced. After calcination in step S15, the whiteness increased again, indicating that impurities were further removed.
[0137] It should be noted that in step S13, 1 mL of dilute sulfuric acid is added to the suspension every 1 to 2 min, and the pH value is measured. In this embodiment, the suspension made of 10.42 g of white lime mud after step S11 is added with 6 mL of 5 mol / L dilute sulfuric acid, and the pH value is close to 7. After adding 1 mL of dilute sulfuric acid again, the pH value suddenly changes, indicating that impurities such as calcium carbonate in the white lime mud are completely reacted.
[0138] In this embodiment, the composition of white lime mud is shown in Table 1.
[0139] Table 1 Main components of white calcium mud
[0140] substance <![CDATA[CaSO4]]> <![CDATA[CaCO3]]> <![CDATA[Fe(OH)3]]> <![CDATA[SiO2]]> <![CDATA[MgCO3]]> Organic matter content(%) 58.07 14.44 3.48 0.40 2.61 21
[0141] In step S11, the process from source wastewater to first-stage wastewater is as follows: Figure 3 The biogas slurry wastewater treatment system shown in the figure comprises a polyferric sulfate reaction tank 1, a lime milk reaction tank 12, and a PAM reaction tank 18 connected in sequence;
[0142] The polyferric sulfate reaction tank 1 is provided with a ferric sulfate reaction tank agitator 6, and is externally connected to a polyferric sulfate dosing barrel 2. A valve 3, a polyferric sulfate dosing pump 4, and a valve 5 are sequentially provided on the connection line; and a biogas slurry addition port is provided on the polyferric sulfate reaction tank 1;
[0143] A lime milk reaction tank mixer 11 is provided inside the lime milk reaction tank 12, and the lime milk dosing tank 7 is connected to the outside. A valve 8, a lime milk metering pump 9, and a valve 10 are provided in sequence on the connection line.
[0144] The PAM reaction tank 18 is provided with a PAM reaction tank agitator 17 inside, and is connected to a PAM dosing barrel 13 outside. The connecting line is provided with a valve 14, a PAM dosing metering pump 15, and a valve 16 in sequence;
[0145] The outlet of the PAM reaction pool 18 is connected to a plate-and-frame feed box 19 , a valve 20 , and a plate-and-frame feed pump 21 in sequence.
[0146] Pump the source wastewater from the biogas slurry inlet to the polyferric sulfate reaction tank 1, open valves 3 and 5, and start the polyferric sulfate dosing pump 4 (the dosage of the polyferric sulfate solution is 33L / m 3 The biogas slurry has an iron content of 11%, and the national standard for polyferric sulfate is GB / t14591-2016. The wastewater continuously enters and exits the polyferric sulfate reaction tank 1, and the hydraulic retention reaction time is 15 minutes. Then it overflows into the lime milk reaction tank 12.
[0147] The wastewater overflows into the lime milk reaction tank 12, valves 8 and 10 are opened, and the lime milk dosing pump 9 is started at the same time (the mass fraction of lime milk is 25%, and the dosage is 6 kg / m3 based on lime (dry basis)). 3 The biogas slurry is continuously introduced into and discharged from the lime milk reaction tank 12, and the hydraulic retention reaction time is 15 minutes.
[0148] The wastewater overflows from the lime milk reaction tank 12 to the PAM reaction tank 18, and valves 14 and 16 are opened, and the PAM dosing pump 16 is started at the same time (the coagulant is added as a liquid PAM solution with a mass fraction of 2.5%, 13L / m 3 The wastewater continuously enters and exits the PAM reaction tank 18, and the hydraulic retention reaction time is 15 minutes.
[0149] Wastewater overflows from the PAM reaction tank 18 to the plate-frame feed box 19 (PP water tank), and the wastewater is temporarily stored in the plate-frame feed barrel. The valve 20 is opened, and the plate-frame feed pump 21 is started to complete the plate-frame feeding. The plate-frame feeding time is 3 to 4 hours. The plate-frame feed pump is used for transportation and squeezing, and the first solid-liquid separation is performed to obtain sedimentation mud (also called iron-calcium mud) and the first section of wastewater (temporarily stored in the PP water tank). The squeezed iron-calcium mud can be used as a processing raw material for the desulfurizer, as shown in Examples 2 to 4 in this specific embodiment.
[0150] It should be noted that the lime is added in the form of lime milk in this embodiment, but in actual implementation, it can also be added in the form of dry CaO.
[0151] The composition of the calcium iron mud is shown in Table 2.
[0152] Table 2 Main components of iron calcium mud
[0153]
[0154] The sludge wastewater contains high alkalinity, colloids, suspended matter, etc. The polyferric sulfate is hydrolyzed and reacts with the sludge to form ferric hydroxide, which plays an adsorption bridging and electrical neutralization role. Organic matter and colloids will be adsorbed and removed. At the same time, iron ions will react with the phosphorus element in the water to produce iron phosphate, which will remove the phosphorus element.
[0155] Ca2+ formed by the added lime 2+ It reacts with sulfate to generate nano-scale calcium sulfate. Lime also reacts with alkalinity to generate calcium carbonate. Organic matter and colloidal substances will coat calcium sulfate and calcium carbonate. In addition, the unreacted lime and the generated calcium sulfate and calcium carbonate will play a certain adsorption and co-precipitation role, making the suspended matter easier to precipitate. It greatly reduces the color of the biogas slurry, greatly improves the sedimentation performance of the biogas slurry, and greatly removes COD and other substances in the biogas slurry.
[0156] Biogas slurry contains a lot of alkalinity. Since the polyferric sulfate solution is acidic and Fe 3+ Hydrolysis also produces H + , first add polyferric sulfate, which can remove most of the alkalinity (Fe 3+ It can react with the alkalinity to generate ferric hydroxide) and reduce the subsequent coagulant dosage, and can react with the lime milk formed by the subsequent addition of lime to obtain ferric hydroxide (excess Fe 3+ With lime provided OH - Reaction), calcium sulfate (SO4 2- With lime provided Ca 2+The reaction generates a mixture mainly composed of CaSO4) and organic matter. After burning at a certain temperature, the organic matter is carbonized and can be used as a raw material for a desulfurizer. The material characterization of the desulfurizer shows that the main components are Fe2O3 and CaSO4. After burning, the iron calcium mud, Fe2O3 and CaSO4 components are close to or even better than the iron content of commercial desulfurizers.
[0157] If lime is added first, calcium carbonate will be generated due to the high alkalinity in the biogas slurry, and the lime dosage is high, which is costly. If polyferric sulfate is added later, the dosage of polyferric sulfate will increase, and the mixed sludge will be mainly composed of calcium carbonate, calcium sulfate and organic matter, which changes the composition. The presence of calcium carbonate reduces the content of Fe2O3, the effective ingredient of the desulfurizer, which is not conducive to subsequent resource recovery. It also increases the cost of biogas slurry treatment.
[0158] In step S12, the first section of wastewater is transferred to a lime reactor, and CaO is added to the wastewater according to the amount of 9 kg of CaO per cubic meter of wastewater, and the pH is adjusted to 11-12. After sufficient mixing, a second solid-liquid separation is performed in an inclined tube sedimentation tank to obtain the second section of wastewater and white lime mud. In this embodiment, the CaO is added by dry addition.
[0159] In step S11, the liquid obtained from the second solid-liquid separation is the second stage wastewater, which can be further processed, such as Figure 4 As shown:
[0160] S16, treating the second wastewater for ammonia nitrogen removal to obtain the third wastewater, and absorbing the ammonia-containing waste gas with dilute sulfuric acid to obtain an ammonium sulfate solution;
[0161] S17, adjust the pH value of the third section wastewater to 8-9, and then carry out biochemical treatment to make the wastewater meet the requirements of the biogas slurry discharge standard.
[0162] In step S16, the second section of wastewater is sprayed downward from the top of the ammonia nitrogen stripping tower, and air is introduced from the aeration device at the bottom of the tower. The gas-liquid ratio is controlled at 2000-3000:1, and the pH is maintained at 11-12 by an automatic alkali addition system. The residence time of the wastewater in the stripping tower is 0.3h to obtain the third section of wastewater. The ammonia-containing tail gas is introduced into the dilute sulfuric acid absorption tower through a pipeline, and is absorbed by a dilute sulfuric acid solution with a concentration of 20-45% to obtain an ammonium sulfate solution.
[0163] The composition of the third stage wastewater is shown in Table 1.
[0164] The composition of the ammonium sulfate solution is tested as shown in Table 3, and can be used to extract ammonium sulfate crystals, which is specifically introduced in Example 5.
[0165] Table 3 Main components of ammonium sulfate
[0166] substance Ammonium sulfate water content(%) 43.70 56.30
[0167] In step S17, CO2 is introduced into the third section of wastewater to adjust the pH to 8-9, and the wastewater is temporarily stored in the biochemical water inlet tank before entering the subsequent biochemical treatment unit. The biochemical treatment process is a multi-stage AO+MBR membrane treatment process connected with a NF nanofiltration treatment process to meet the requirements of the biogas slurry discharge standard.
[0168] The main pollutant components in the source wastewater and the pollutant components of the wastewater in each section in this embodiment are shown in Table 4.
[0169] Table 4 Pollutant components in each stage of wastewater treatment in biogas slurry
[0170]
[0171] The composition of the discharged wastewater is shown in Table 1.
[0172] The biogas slurry discharged by the present invention meets the Class A standard of urban sewage treatment plants. Different customers implement different standards, and the implementation standards change according to environmental impact assessments. The present invention also meets other standards, such as the pollutant discharge standards for livestock and poultry farming, the Class B water quality standard for sewage discharged into urban sewers, and the comprehensive sewage discharge standard.
[0173] In the field of biogas slurry wastewater treatment, PAC (polyaluminium chloride) is traditionally used as a coagulant to achieve the flocculation and sedimentation process. However, PAC has some limitations during use. For example, the stability of the aluminium hydroxide colloid produced by its hydrolysis is easily affected by water quality conditions. A certain amount of chloride ions may remain in the water after treatment. In the long run, there are potential risks to the environment and subsequent reuse, and the treatment cost is relatively high.
[0174] The present invention abandons the traditional use of PAC, and innovatively selects polyferric sulfate and calcium oxide as alternative coagulants for combination in the treatment of biogas slurry wastewater. Polyferric sulfate has excellent coagulation performance. It can quickly hydrolyze in water to form a large amount of iron hydroxide oxide and iron hydroxide colloids. These colloids have a large specific surface area and a strong adsorption capacity. They can effectively adsorb pollutants such as suspended particles, organic matter and some heavy metal ions in the wastewater, so that they can condense to form larger flocs, which are convenient for subsequent precipitation and separation. On the one hand, calcium oxide can adjust the pH value of the wastewater and create an acid-base environment that is conducive to the best coagulation effect of polyferric sulfate; on the other hand, the calcium ions produced by the hydrolysis of calcium oxide can also participate in the flocculation process, and through adsorption and electrical neutralization with the colloidal particles in the wastewater, the flocculation and precipitation effect is further enhanced, and the removal of pollutants is promoted.
[0175] Detection and analysis
[0176] The main components of calcium sulfate samples were tested by XRD, and the results are as follows: Figure 5It can be seen that the organic impurities attached to the white lime mud are significantly removed after pickling and calcination, and the impurities in the calcium sulfate sample are significantly reduced. The main component is calcium sulfate, with a content of 99.1wt.%, with excellent whiteness value and high product purity.
[0177] The calcium sulfate samples were tested according to the industry standard HG / T 5346-2018 in an environment of 20-23°C and 49-51% RH. The results are shown in Table 5.
[0178] Table 5 Calcium sulfate sample test results
[0179]
[0180] The morphology of calcium sulfate samples was examined by SEM. Figure 6 As shown, it can be seen that the calcium sulfate crystals are better. Compared with the traditional calcium sulfate preparation method, the product purity and whiteness of this embodiment have great advantages.
[0181] This specific embodiment also provides a method for preparing a desulfurizer, which is prepared by using the iron calcium mud in the above-mentioned method for preparing calcium sulfate using biogas wastewater, and is specifically introduced through Examples 2 to 4.
[0182] Example 2
[0183] This example provides a method for preparing a hydroxyl-containing iron oxide desulfurizer using the iron calcium mud obtained in Example 1.
[0184] S21, drying the calcium iron mud in an oven at 100° C. to constant weight, cooling naturally, and then crushing it with a crusher, passing it through a 200-mesh sieve, and retaining the sieved material;
[0185] S22, the sieved iron calcium mud was placed in a corundum crucible, placed in a muffle furnace, calcined at 200 ° C for 2 hours in the presence of oxygen, cooled to room temperature, and the calcination weight loss was measured to be 27.3% (calcination weight loss = 煅烧前 煅 重 烧 量 前 — 重 煅烧 量 后重量 ), photos of samples before and after calcination are shown in Figure 7 As shown;
[0186] S23, the calcined iron calcium mud was added to a 12.5 mol / L NaOH aqueous solution to obtain an iron calcium mud slurry with a solid content of 30%, the slurry was stirred at a speed of 500 rpm using a magnetic stirrer for 1 hour, and then the solid-liquid separation was performed, and then the slurry was fully rinsed with deionized water to neutrality, and the solid-liquid separation was performed again, and then the alkali-washed iron calcium mud was dried in an oven at 105°C to constant weight to obtain the alkali-washed iron calcium mud, and the alkali-washing weight loss was 28.49% ( The weights here are all dry weights);
[0187] S24, grinding the ferric calcium mud after alkali washing, passing it through a 200-mesh sieve, retaining the sieve residue, and obtaining a hydroxy-containing iron oxide desulfurizer.
[0188] The morphology of the iron oxyhydroxide desulfurizer measured by SEM on the sample ground and sieved through 200 mesh is as follows: Figure 8 and Fig. 9 As shown. The brighter substance is iron oxyhydroxide, and the darker substance is calcium sulfate. During the calcination process, in the presence of high temperature and oxygen, the organic matter undergoes volatilization, combustion and other processes to generate gaseous products such as CO2 and water. These gaseous products form a certain pressure inside the inorganic salt and then escape, leaving pores in the inorganic salt.
[0189] The composition of the desulfurizer containing iron oxide containing hydroxyl measured by XRF is shown in Table 6.
[0190] Table 6 XRF results of desulfurizer containing iron oxyhydroxide
[0191] substance <![CDATA[SiO2]]> <![CDATA[SO3]]> CaO <h2 style=";text-align:left;direction:ltr"><![CDATA[F <h2 style=";text-align:left;direction:ltr"> e2 <h2 style=";text-align:left;direction:ltr"> O3]]><h2 style=";text-align:left;direction:ltr"> other content(%) 2.06 19.88 21.56 52.95 3.55
[0192] XRD is mainly used to analyze crystal structure. For materials with poor crystallinity and amorphous state, the diffraction peaks produced are weak, diffuse or even absent. The spectra of the calcined iron calcium mud in step S22 and the oxyhydroxide-containing iron desulfurizer in step S24 were measured by XRD as follows: Fig.10 As shown, it can be seen that the main components are calcium sulfate, calcium carbonate and iron oxyhydroxide. Among them, iron oxyhydroxide mainly exists in amorphous form, so it cannot be clearly shown in the XRD spectrum. Colloidal iron oxyhydroxide is difficult to show clearly in XRD mainly because the particle size is small in the amorphous state and there may be a large amount of amorphous parts.
[0193] The composition of the iron oxyhydroxide-containing desulfurizing agent prepared in this embodiment is as follows:
[0194] Calcium sulfate: 31.35 parts;
[0195] Iron oxyhydroxide: 56.08 parts;
[0196] Impurities: 12.57 parts.
[0197] As an embodiment, the impurities include SiO2, CaCO3, and MgCO3.
[0198] In this embodiment, the samples obtained in each step were subjected to a desulfurization performance evaluation test, and the H2S standard gas concentration used was 20000 ppm, and the balance gas was N2.
[0199] Although the dried calcium iron mud in step S21 also contains iron oxyhydroxide, its surface is covered by a large amount of organic matter, resulting in poor desulfurization effect, and the breakthrough sulfur capacity is only 0.41%;
[0200] The calcined but not alkali-washed iron-calcium mud was ground and passed through a 200-mesh sieve for a desulfurization performance evaluation test. The penetration sulfur capacity was 10.12%. It can be seen that after calcination, the organic matter volatilized and decomposed by about 27.3%, allowing the iron oxyhydroxide to contact the sulfur in the gas, thereby achieving a desulfurization effect.
[0201] The breakthrough sulfur capacity of the ferric oxide desulfurizer containing hydroxyl obtained in step S24 is 20.10%. It can be seen that after the alkaline washing treatment, the removal rate of organic matter is higher, which further improves the desulfurization effect of the ferric oxide desulfurizer containing hydroxyl.
[0202] The present embodiment provides a method for preparing a desulfurizer containing hydroxyl iron using biogas wastewater, which not only retains the active substance of hydroxyl iron, but also realizes the removal of organic matter, and in the process of removing organic matter, a pore is generated in the crystal of Ca-containing inorganic salt, which is suitable for use in biogas and biomass natural gas desulfurization and other related fields. From the perspective of structural stability, calcium sulfate and calcium carbonate can be filled between hydroxyl iron particles to play a supporting and stabilizing role. In the desulfurization process, the desulfurizer needs to withstand complex working conditions such as high temperature and gas scouring. The addition of calcium salt can prevent the agglomeration and sintering of hydroxyl iron particles, maintain the good pore structure of the desulfurizer, and ensure that the gas can smoothly enter the interior of the desulfurizer and contact with the active ingredients. The desulfurizer containing hydroxyl iron prepared by the present invention has excellent desulfurization efficiency and service life.
[0203] Example 3
[0204] This example provides a method for using the iron-calcium mud obtained in Example 1 to prepare a carbon / γ-iron oxide chimera desulfurizer.
[0205] S31, drying the calcium iron mud in an oven at 105° C. to constant weight, and cooling naturally;
[0206] S32, place the dried calcium iron mud in a corundum crucible, fully shake and level the powder surface, and manually compact it with the crucible cover. In this embodiment, the density after pressing is 3.1 g / cm 3Then, the crucible (with crucible cover) was placed in a muffle furnace and calcined at 600°C for 3 hours without oxygen to obtain a black solid product. After measurement, the calcination weight loss was 33.22%. The photos before and after calcination are shown in FIG. Fig.11 As shown;
[0207] S33, the black solid product was placed in a box-type electric furnace, calcined at 400°C in air for 2 hours, and then cooled to room temperature to obtain a black-red carbon / γFe2O3 chimera crude product. The photo after calcination is as follows: Fig.12 As shown;
[0208] S34, grinding the crude product, passing it through a 200-mesh sieve, retaining the sieve residue, and obtaining a carbon / γFe2O3 chimera desulfurizer.
[0209] In step S32, since the crucible cover and the crucible, and the crucible cover and the powder in the crucible are tightly connected, a relatively closed space is formed, which acts as a physical barrier to the air. During the calcination process, the amount of air entering will be very small. When the organic matter in the iron calcium mud in the crucible is calcined, the organic matter decomposes into gases such as ammonia and hydrogen, leaving carbonaceous components, which will also reduce the amount of air entering when the gas escapes. FeOOH decomposes into Fe2O3 at high temperature, and since the decomposed gas is reducing, during the oxygen-isolated calcination process, Fe2O3 is reduced to Fe3O4, and the carbonaceous components are coated on the surface of Fe3O4, that is, the obtained black solid product.
[0210] In step S33, since the calcination temperature is not high, some carbon produced by carbonization of organic matter still adheres to the surface of γ-Fe2O3, forming a crude carbon-γ iron oxide chimera product.
[0211] Detection and analysis
[0212] By using XRD to detect the main components of the carbon / γ iron oxide chimera desulfurizer, it can be seen that the crystals in the sample are CaCO3, CaSO4, and γFe2O3, and the mass ratio between the three is 1:3.45:5.55.
[0213] The carbon / γ-iron oxide chimera desulfurizer prepared in this example has the following components by weight:
[0214] Carbon: 15.18 parts;
[0215] Gamma iron oxide: 45.33 parts;
[0216] Calcium sulfate: 28.19 parts;
[0217] Calcium carbonate: 8.16 parts;
[0218] Impurities: 3.14 parts, including SiO2 and MgCO3.
[0219] The morphology of the carbon / γFe2O3 chimera desulfurizer was measured by SEM. Fig.13 As shown, it can be seen that the better crystal form is the γ iron oxide crystal, the activated carbon material and the γ iron oxide are embedded together, the γ iron oxide has a higher sulfur removal effect, and the activated carbon material has a large specific surface area and rich pore structure, which can adsorb H2S in the gas; the γ iron oxide also has a higher sulfur removal effect, so the carbon / γ iron oxide mosaic desulfurizer can be used as a desulfurizer. The desulfurization performance evaluation test was carried out, and the test method was the same as in Example 1, and the breakthrough sulfur capacity of the carbon / γ iron oxide mosaic desulfurizer reached 15.6%.
[0220] When the dried calcium iron mud in this embodiment is calcined at 600°C in an oxygen-free environment, FeOOH is first decomposed into Fe2O3, and then reduced to Fe3O4 by the gas formed by the decomposition and carbonization of organic matter, while the carbon material decomposed by the organic matter is coated around Fe3O4. After further aerobic calcination at 400°C, Fe3O4 is converted into γ iron oxide, which forms a carbon / γ iron oxide chimera with the carbon generated by the decomposition of organic matter, and can be used as a desulfurizer.
[0221] The present invention uses iron calcium mud to prepare a carbon / γ iron oxide chimera desulfurizer. First, the iron calcium mud is calcined in an oxygen-free state. The reducing gas generated during the decomposition of organic matter reduces the iron oxide in the iron calcium mud to ferroferric oxide, and the decomposed carbon component is coated on the ferroferric oxide particles, and then calcined in an oxygen-free state to obtain a carbon / γ iron oxide chimera. This structure can not only improve the stability of the material and prevent the loss of active ingredients, but also give the material good adsorption properties and the like.
[0222] Example 4
[0223] This example provides another method for using the iron-calcium mud obtained in Example 1 to prepare a carbon / γ-iron oxide chimera desulfurizer.
[0224] The dried calcium iron mud was placed in a hydrothermal reactor, deionized water was added, and the solid-liquid mass ratio was 1:5, and the reactor was sealed; the reactor was then placed in an oven at 200°C, the pressure in the reactor increased, and after the hydrothermal treatment for 4 hours, the reactor was cooled to room temperature;
[0225] After the hydrothermal treatment, the ferric calcium mud slurry is separated from the solid and liquid. After solid-liquid separation, drying, grinding and passing through a 200-mesh sieve, the hydrothermal ferric calcium mud, i.e., ferric calcium mud containing Fe3O4, is obtained. A certain amount of ferric calcium mud containing Fe3O4 is weighed into a corundum crucible, and placed in a muffle furnace for aerobic calcination. The temperature is raised to 280°C at a rate of 10°C / min, and after keeping warm for 2h, it is cooled to room temperature. The obtained product is ground and crushed to obtain a carbon / γ-iron oxide chimera desulfurizer below 200 mesh.
[0226] The carbon / γ-iron oxide chimera desulfurizer prepared in this example has the following components by weight:
[0227] Carbon: 16.28 parts;
[0228] Gamma iron oxide: 45.33 parts;
[0229] Calcium sulfate: 27.19 parts;
[0230] Calcium carbonate: 8.11 parts;
[0231] Impurities: 3.09 parts, including SiO2 and MgCO3.
[0232] In terms of economic benefits, the production cost of the desulfurizer is significantly reduced by using waste as raw materials. Compared with the desulfurizer prepared by the traditional pure chemical synthesis method, the desulfurizer prepared by the present invention has obvious advantages in raw material procurement cost and preparation process. In the traditional process, calcium sulfate and other catalysts need to be mixed, which is complicated and costly.
[0233] This specific embodiment also provides a method for preparing ammonium sulfate, which is prepared using the ammonium sulfate solution obtained in the above-mentioned method for preparing calcium sulfate using biogas wastewater, and is specifically introduced through Example 5.
[0234] Example 5
[0235] In this embodiment, a method for preparing ammonium sulfate using the ammonium sulfate solution obtained in Example 1 is provided, comprising the following steps:
[0236] S51, add an ethanol solution with a concentration of not less than 75vol.% (industrial ethanol is used in this embodiment, and the solvent is water) to the ammonium sulfate solution at a rate of 5-20mL / min (5mL / min in this embodiment), and continue stirring during this period. Because the solubility of ammonium sulfate in ethanol is low, with the continuous addition of ethanol, the solution will gradually become turbid, ammonium sulfate crystals will begin to precipitate, and the mixed solution will be stratified. Stir continuously with a glass rod, and continue to add ethanol solution until the mixed solution no longer has stratification, and the ammonium sulfate crystals in the solution have completely precipitated. Then use a funnel to filter the crystallized solution, and use filter paper to separate the ammonium sulfate crystals from the solution. When filtering, pay attention to let the end of the funnel neck fit closely to the inner wall of the receiving container to avoid splashing of the filtrate. After the solid-liquid separation is completed, a small amount of ethanol is used to wash the ammonium sulfate crystals on the filter paper to remove residual impurities on the crystal surface. In this embodiment, the mass ratio of the added ethanol solution to the ammonium sulfate solution is set to 1.5:1.
[0237] S52, transfer the washed ammonium sulfate crystals to an evaporating dish and dry them naturally at room temperature until the mass of the ammonium sulfate crystals remains constant, so that relatively pure ammonium sulfate crystals can be obtained. Of course, the drying method can also be selected to be drying at 50°C or vacuum drying, which will not be elaborated here.
[0238] S53. The solution produced by solid-liquid separation is a mixture of ethanol and water. The two are separated by means of a pervaporation membrane. The separated ethanol can be recycled and the water can be reused, which helps to reduce operating costs and reduce the waste of water resources.
[0239] Detection and analysis
[0240] The ammonium sulfate sample prepared in this embodiment was tested for composition according to standard GB / T 1396-2015, and the testing environment was 20-23° C. and 49-51% RH. The results are shown in Table 7.
[0241] Table 7 ammonium sulfate sample test results
[0242]
[0243] The purity of the ammonium sulfate crystals obtained in step S32 is tested, and it is found that the purity reaches 99.8%. The purity of most ammonium sulfate crystals on the market is between 90% and 98%. The ammonium sulfate crystals prepared by the present invention have a higher purity. At the same time, compared with the traditional ammonium sulfate crystal preparation method, the present method has the advantages of greatly reducing energy consumption in the production process, simple production process flow and less environmental pollution, and also has the benefits of recycling and reducing resource waste.
[0244] The present invention also provides a method for preparing ammonium sulfate by purifying ammonium sulfate solution, using the ammonium sulfate solution produced by biogas slurry treatment as a raw material, and preparing ammonium sulfate crystals through a series of processing. The results show that the ammonium sulfate crystals prepared by using the ammonium sulfate solution produced by biogas slurry treatment are of good crystal form and high purity. The present invention provides a process for preparing ammonium sulfate crystals by using the ammonium sulfate solution produced by biogas slurry treatment with good stability and economy, which provides a new idea for the treatment of the ammonium sulfate solution produced in biogas slurry treatment and the preparation method of ammonium sulfate crystals.
[0245] In summary, from the perspective of resource recovery, the present invention not only utilizes the biogas slurry wastewater to prepare a variety of products, such as hydroxyl iron oxide desulfurizer, carbon / γ iron oxide chimera desulfurizer, calcium sulfate, ammonium sulfate, humus, etc., but also effectively treats the biogas slurry wastewater during the preparation process to meet the emission standards, thereby realizing the resource recycling of waste.
[0246] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A method for preparing calcium sulfate using biogas slurry wastewater, characterized in that: The following steps are involved: The dried white lime mud powder and deionized water are prepared into a suspension with a solid content of 15-25%; the suspension is added with dilute sulfuric acid at 60-100° C. for sufficient reaction, and the reaction product is filtered, washed and dried to obtain an intermediate sample; the intermediate sample is calcined at 300-400° C. for 1.5-2.5 hours, and after cooling, the calcium sulfate is obtained; The white lime mud is obtained by using biogas slurry wastewater. After the biogas slurry wastewater is flocculated and precipitated, an alkaline substance is used for pH adjustment treatment, and then solid-liquid separation is performed. The obtained precipitated mud is the white lime mud, and the alkaline substance is calcium oxide.
2. The method for preparing calcium sulfate using biogas slurry wastewater according to claim 1, characterized in that: The white lime mud obtained in the process of treating biogas wastewater is used to prepare the calcium sulfate. The components of the white lime mud are as follows by mass: 52 to 64 parts of calcium sulfate, 12 to 16 parts of calcium carbonate, and 23 to 33 parts of impurities, wherein the impurities include ferric hydroxide, silicon oxide, magnesium carbonate and organic matter.
3. The method for preparing calcium sulfate using biogas slurry wastewater according to claim 2, characterized in that: The impurities include 3 to 5 parts of iron hydroxide, 0.3 to 0.5 parts of silicon oxide, 2.3 to 3 parts of magnesium carbonate and 18 to 24 parts of organic matter.
4. The method for preparing calcium sulfate using biogas slurry wastewater according to claim 1, characterized in that: The dried white lime mud is ground and pulverized to obtain white lime mud powder with a mesh size of 200 or finer, and then the suspension is prepared.
5. The method for preparing calcium sulfate using biogas slurry wastewater according to claim 1, characterized in that: The concentration of the dilute sulfuric acid is 4-6 mol / L.
6. The method for preparing calcium sulfate using biogas slurry wastewater according to claim 1, characterized in that: The pH value is used to determine whether the reaction is complete. When the pH value of the reaction system is close to 7, the pH value changes suddenly after adding dilute sulfuric acid again, indicating that the reaction is complete.
7. The method for preparing calcium sulfate using biogas slurry wastewater according to claim 6, characterized in that: The dilute sulfuric acid is added in a stepwise manner, with 1 to 2 mL added each time, and the pH value is tested after sufficient stirring.
8. The method for preparing calcium sulfate using biogas slurry wastewater according to claim 1, characterized in that: The solid content of the suspension is 20%, the concentration of the dilute sulfuric acid is 5 mol / L, the reaction temperature of adding dilute sulfuric acid into the suspension is 80° C., the temperature of the calcination treatment is 350° C., and the calcination time is 2 h.
9. The method for preparing calcium sulfate using biogas slurry wastewater according to any one of claims 1 to 8, characterized in that: It is also possible to co-produce one or more of a hydroxyl-containing iron oxide desulfurizer, a carbon / γ iron oxide desulfurizer, and ammonium sulfate.
10. A calcium sulfate, characterized in that The calcium sulfate is prepared by the method for preparing calcium sulfate by utilizing biogas wastewater as claimed in any one of claims 1 to 9, wherein the calcium sulfate has a purity of not less than 99.1wt.% and a whiteness of more than 95%.
Citation Information
Patent Citations
A method for continuous preparation of calcium sulfate whiskers
CN114197028B